Risk factors, morbidity and mortality of neonatal tetanus - Dey, AC; Saha, L; Shahidullah, M (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):54-58 The abstract of this article is available on the PubMed website